Effects of water vapor and nitrogen on oxidation of TNM alloy at 650 °C. (September 2019) - Shaaban, Ali; Hayashi, Shigenari; Takeyama, Masao
Highlights: Non-protective Al/Ti mixed oxide scale forms on TNM alloy at 650 °C. Water vapour negatively affects the oxidation protection of TNM alloy at 650 °C. N2 in oxidizing atmosphere mitigates the detrimental effect of water vapour. Protective amorphous Al2 O3 layer reduces the oxidation rate of the TNM alloy. Nitride layer maintains the amorphous Al2 O3 layer for longer oxidation time. Abstract: The effect of water vapor on the oxidation behavior of a TiAl alloy, TNM, was investigated at 650 °C. The oxidation mass gains were four times higher in wet Ar and twice as high in wet air than in the corresponding dry atmospheres. No external Al2 O3 formed during oxidation in different atmospheres after 500 h. TEM revealed that multi-layered oxide scales were formed by oxidation in different atmospheres. An amorphous Al-rich oxide layer that was stabilized by the formation of a Ti(Al)N layer provided better protection against oxidation of the TNM alloy in air than in a water vapor-containing atmosphere.